2014
DOI: 10.1038/ismej.2014.12
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria, phages and pigs: the effects of in-feed antibiotics on the microbiome at different gut locations

Abstract: Disturbance of the beneficial gut microbial community is a potential collateral effect of antibiotics, which have many uses in animal agriculture (disease treatment or prevention and feed efficiency improvement). Understanding antibiotic effects on bacterial communities at different intestinal locations is essential to realize the full benefits and consequences of in-feed antibiotics. In this study, we defined the lumenal and mucosal bacterial communities from the small intestine (ileum) and large intestine (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

70
274
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 330 publications
(346 citation statements)
references
References 59 publications
(75 reference statements)
70
274
1
1
Order By: Relevance
“…Another study from Looft and colleagues reported ϳ20 to 30% Firmicutes and 50 to 60% Bacteroidetes in animals weaned at 12 days and tested at 8 weeks (58). One explanation for the dominance of the Firmicutes in our study is the use of terminal small ileum samples rather than fecal samples, and that explanation is supported by a recent study examining the composition of the microbiota in several segments of the porcine GI tract: here, the ileal microbiota was ϳ95% Firmicutes, whereas the cecal, colonic, and fecal flora was ϳ50% Bacteroidetes (30).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Another study from Looft and colleagues reported ϳ20 to 30% Firmicutes and 50 to 60% Bacteroidetes in animals weaned at 12 days and tested at 8 weeks (58). One explanation for the dominance of the Firmicutes in our study is the use of terminal small ileum samples rather than fecal samples, and that explanation is supported by a recent study examining the composition of the microbiota in several segments of the porcine GI tract: here, the ileal microbiota was ϳ95% Firmicutes, whereas the cecal, colonic, and fecal flora was ϳ50% Bacteroidetes (30).…”
Section: Discussionsupporting
confidence: 74%
“…In light of this, it was hypothesized that feeding of enzymes and substrate should allow the enzymatic degradation of highly complex molecules into prebiotic fibers in situ, thereby decreasing the issues of industrial fiber production, such as purification and transport. Release of these fibers from potato pulp by the gut microbiota is not possible, as the bacteria in the pig ileum do not possess genes for pectinolytic enzymes (30).…”
mentioning
confidence: 99%
“…Similar results were suggested by several previous researchers (Looft et al 2014;Kamada et al 2013;Sekelja et al 2012;Videnska et al 2013); for example, Looft et al reported that ileum, cecum, mid-colon and feces have different microbial communities in swine at the phylum and genus level (Looft et al 2014). Sekelja et al also reported that a clear separation of microbial composition was seen between the upper gut (crop and gizzard), ileum and lower gut (cecum and colon) in broiler chickens (Sekelja et al 2012).…”
Section: Discussionsupporting
confidence: 79%
“…In pigs, the ileal mucosa harbors greater bacterial diversity than the lumen and has a makeup similar to that of the mucosa of the large intestine, suggesting that mucosal microbes of the ileum serve as an inoculum for the large intestine (12). High-dose BLS mix treatment increases the abundance of members of the phylum Proteobacteria during F4 ϩ ETEC infection, raising the possibility that excessive BLS mix treatment increases the risk for enteritis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, culture or targeted molecular biology-based analyses provide an incomplete profile of the microbiota. Next-generation high-throughput sequencing of PCR amplicons from the 16S rRNA genes has been used for high-resolution surveys of microbiota communities, and this technological development has facilitated detailed analysis of the microbiota structure (12). The microbial ecosystem of the swine gut changes across growth stages, and these variations in the gut microbiota are driven by a variety of factors, including exogenous bacteria (13).…”
mentioning
confidence: 99%